2022
DOI: 10.1007/s11033-022-07542-7
|View full text |Cite
|
Sign up to set email alerts
|

OXR1 signaling pathway as a possible mechanism of elastase-induced oxidative damage in pulmonary cells: the protective role of ellagic acid

Abstract: Background and objective: Oxidative stress is a process that occurs through free radicals on the cell membranes which causes damage to the cell and intracellular organelles especially mitochondria membranes. H2O2 induced oxidative stress in human cells is of interest in toxicological research since oxidative stress plays a main role in the etiology of several pathological conditions. Neutrophil Elastase (Serine proteinase) is involved in the pathology process of emphysema as a respiratory disease through lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…out of the ten compounds identified by LC-MS/MS, ellagic acid and gallic acid are known to reduce emphysema in mice and rats. Studies conducted by various groups showed that ellagic acid can prevent inflammation and oxidative stress in elastase-induced emphysema model in rat ( Mansouri et al, 2020 ; Sohrabi et al, 2021 ) and reduce oxidative stress in pulmonary cells induced by elastase ( Bayati et al, 2022 ) . Previous reports also show that gallic acid can ameliorate COPD linked lung inflammation and emphysema in mice ( Singla et al, 2020 ; Wu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…out of the ten compounds identified by LC-MS/MS, ellagic acid and gallic acid are known to reduce emphysema in mice and rats. Studies conducted by various groups showed that ellagic acid can prevent inflammation and oxidative stress in elastase-induced emphysema model in rat ( Mansouri et al, 2020 ; Sohrabi et al, 2021 ) and reduce oxidative stress in pulmonary cells induced by elastase ( Bayati et al, 2022 ) . Previous reports also show that gallic acid can ameliorate COPD linked lung inflammation and emphysema in mice ( Singla et al, 2020 ; Wu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, they secrete many types of proteinases and ROS, which injure alveolar epithelial cells and reduce the levels of surface proteins. Both of them are important for gas exchange [ 70 ]. They also cause blood vessel damages by impairing vessel permeability.…”
Section: Macrophages and Their Function In Alimentioning
confidence: 99%
“…Polarization towards the proinflammatory M1 phenotype is regulated by many factors. Studies have demonstrated the important roles of suppressor of cytokine signaling 3 (SOCS3), NF-κB and so on in this process [ 70 , 73 ]. In addition, c-Jun N-terminal kinase (JNK) is interesting because it has a dual effect on the polarization of macrophages.…”
Section: Macrophages and Their Function In Alimentioning
confidence: 99%